2019
DOI: 10.1002/brb3.1229
|View full text |Cite
|
Sign up to set email alerts
|

A resting‐state study of volumetric and functional connectivity of the habenular nucleus in treatment‐resistant depression patients

Abstract: Objective To investigate the volumetric and functional connectivity of the habenular nucleus in treatment‐resistant depression (TRD) patients using the resting‐state functional magnetic resonance imaging (rs‐fMRI) approach. Methods A total of 15 TRD patients, who visited the Mental Health Institute of the First Hospital Affiliated with Jilin University between August 2014 and March 2015, along with 15 normal subjects, were enrolled into this study for structural and functional imaging. Functional connectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 67 publications
(67 reference statements)
0
28
0
Order By: Relevance
“…7,35,43 These findings have been extended to the pathophysiology of TRD. 10,[44][45][46] However, fewer studies have reported a relationship between changes in RSFC and treatment response heterogeneity in TRD patients. 18,47,48 In this study, the seed-based exploratory analysis at baseline revealed a cluster that was associated with treatment response to ketamine within the AN, but not the DMN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,35,43 These findings have been extended to the pathophysiology of TRD. 10,[44][45][46] However, fewer studies have reported a relationship between changes in RSFC and treatment response heterogeneity in TRD patients. 18,47,48 In this study, the seed-based exploratory analysis at baseline revealed a cluster that was associated with treatment response to ketamine within the AN, but not the DMN.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 35 , 43 These findings have been extended to the pathophysiology of TRD. 10 , 44 , 45 , 46 However, fewer studies have reported a relationship between changes in RSFC and treatment response heterogeneity in TRD patients. 18 , 47 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…Previous fMRI studies indicate that abnormal circuitry underlying TRD may involve the affective, salience, auditory, visual networks, and the language processing cortex ( He et al, 2016 ). Recent studies have shown, more specifically, abnormal functional connectivity (FC) in the habenular nucleus ( Amiri et al, 2021 ), especially with the default mode network (DMN) ( Luan et al, 2019 ) in TRD patients. This is very interesting given the putative functions of the habenula.…”
Section: Introductionmentioning
confidence: 99%
“…It is an epithalamic structure and anatomical hub located at the center of the dorsal diencephalic conduction system, a pathway linking the forebrain to midbrain regions [9]. The Hb is considered to be related to punishment and motor activity during reward processes and the adaptive response to stress [10,11], and based on previous experiments with animals, it is hypothesized to play an important role in controlling emotions; notably, the overactivation of the Hb is reported to be associated with depression [12][13][14]. Consistent with the monoamine hypothesis of MDD, the Hb is thought to regulate the activity of ascending monoaminergic projections from the brainstem [15], and increased metabolism of the Hb has been observed in animal models of stress and depression [16].…”
Section: Introductionmentioning
confidence: 99%